T-lymphocyte subsets as a predictive biomarker for stroke-associated pneumonia - Feng, Hong-Xuan (Am J Transl Res, 2018)
The aim of this study was to facilitate the clinical treatment and prognosis of stroke-associated pneumonia (SAP) by examining changes in T-lymphocyte subsets. Stroke patients admitted in Suzhou Hospital between 2014 and 2016 participated in the study. Patients were divided into a pneumonia group (50 patients) and a non-pneumonia group (254 patients) based on a diagnosis of pneumonia. Information regarding risk factors for ischemic stroke was collected from all patients using a questionnaire. Compared with non-SAP patients, SAP patients were older, dysphagic, smokers, had higher NIH stroke scale (NIHSS) scores and neutrophil: lymphocyte ratio, had higher leukocyte, neutrophil, and CD8 levels, had lower CD3, CD4, and lymphocyte levels, and had a lower CD4:CD8 ratio. Patients with a higher NIHSS score had higher CD8 levels, lower CD3 and CD4 levels, and a lower CD4:CD8 ratio. No significant differences in T-lymphocyte subsets were found between the left and right cerebral hemispheres. After adjusting for other variables, smoking, dysphagia, NIHSS score, and CD4:CD8 ratio were positively associated with SAP. The areas under the receiver operating characteristic curve for dysphagia, NIHSS score, CD4:CD8 ratio, CD4:CD8 ratio + NIHSS score, and Dysphagia+ CD4:CD8 ratio + NIHSS score were 0.583 (95% CI: 0.490-0.675), 0.791 (95% CI: 0.724-0.859), 0.676 (95% CI: 0.593-0.759), 0.846 (95% CI: 0.790-0.902), and 0.867 (95% CI: 0.815-0.918), respectively. A few T-lymphocyte subsets may increase susceptibility to pneumonia after acute ischemic stroke. Thus, the detection of T-lymphocyte subsets may predict the risk of SAP in such patients.